Teaching and educational activity of V. Lihin (1846 – 1900) - O. A. Oliinyk (History of science and technology, 2018)
The article reveals little-known facts from the life and work of V. Lihin (1846-1900). A tal-ented scientist, devoted to his work as a teacher, a public figure with an extraordinary talent of the administrator. His educational activities had a significant impact on the development of the econo-my and industry in Odessa, and then the entire region. Нe paid a lot of attention to the sessions with students, developed manuals, prepared lists of recommended literature. Lihin believed that education was a major factor in the development of economy and society. At the end of his teaching career, Lihin became the mayor of Odessa. In this position, he paid much attention to the development of the city and to meet its needs. In 1896 the Lihin did everything possible to open a medical faculty in Odessa. The faculty was to provide doctors with the entire South of Ukraine and the Caucasus. In 1897 he was appointed as the head of the educational district in Warsaw. Here he met a number of problems.Valerian Lihin truly believed that it’s extremely important for people of all nation to study their native language and culture. He helped to preserve the Polish language as a discipline in elementary school.